Suppression of hole decoherence in ultrafast photoionization - Karamatskou, Antonia; Goetz, R. Esteban; Koch, Christiane P.; Santra, Robin (Physical Review A, 2020)
In simple one-photon ionization, decoherence occurs due to entanglement between ion and photoelectron. Therefore, the preparation of coherent superpositions of electronic eigenstates of the hole in the photoion is extremely difficult. We demonstrate for the xenon atom that the degree of electronic coherence of the photoion in attosecond photoionization can be enhanced if the influence of many-body interactions is properly controlled. A mechanism at low photon energies involving multiphoton ionization is found, suppressing the loss of coherence through ionization into the same photoelectron partial waves. The degree of coherence found between the 4d0 and 5s hole states is, on the one hand, limited by Auger decay of the 4d0 hole. On the other hand, increasing the population ratio such that a significant portion of the state is in a true superposition of both states renders the maximization of the degree of coherence difficult.
CRIS-Team Scopus Importer:2023-04-20